Integration of the Ethno-Discovery Project and Ethno-Design Literacy: A Contextual Syntax Model in Quality Ornamental Learning - Ilham Zamil; Puspaneli; Hari Setia Putra; Hamsidar; Molli Wahyuni; Yusmerita; Yuliarma; Lili Mulyani (Postgraduate, University of Mataram, 2026)
Creativity and plagiarism remain key challenges in learning Ragam Hias (Decorative Motif Design). Common problems include repetitive ideas, reliance on peers’ work, limited originality, and low self-confidence. Additionally, existing learning models often lack relevance to students’ needs, while assessment standards are not tailored to course characteristics. This study aimed to develop and evaluate the Ethno Discovery Project syntax integrated with Ethno-Design literacy. The development process involved validation, practicality, and effectiveness testing across three student groups. Expert validation showed good validity (0.71) and high reliability (ICC = 0.775). Practicality was rated very good by both observers (0.79) and students (0.77). Effectiveness testing revealed a significant increase in student scores from 5.45 to 9.77 (p < 0.001), with high learning activity (82.22%) and interest (81.58%). The results indicate that this syntax is effective, applicable, and culturally relevant for contextual learning in vocational design education.